Predictors of mortality in patients with COPD after 9 years - Prudente, Robson [UNESP]; Franco, Estefânia Aparecida Thomé [UNESP]; Mesquita, Carolina Bonfanti [UNESP]; Ferrari, Renata [UNESP]; De Godoy, Irma [UNESP]; Tanni, Suzana Eerico [UNESP] (Taylor & Francis, 2018)
Background: COPD is one of the leading causes of morbidity and mortality in the world; however, the most varied amounts of clinical and laboratory characteristics acts in different ways in the mortality among over time. Therefore, this study aimed to evaluate the predictors of mortality in patients with COPD after 9 years. Patients and methods: One hundred and thirty-three patients with COPD were assessed at baseline by spirometry, pulse oximetry (SpO 2 ), body composition, intensity of dyspnea, distance walked in the 6-minute walk test (6MWT), and Charlson Comorbidity Index (CCI). Results: After 9 years, it was not possible to identify the lifetime of 4 patients who died and of 19 patients who stopped follow-up; thus, 110 patients were included in the analysis of predictors of mortality (67% male, 65±9 years old, and FEV 1 : 52.5 [40%-73%]). Male sex, age, SpO2, Body mass index, airway Obstruction, Dyspnea, and Exercise capacity (BODE) index, and frequency of exacerbations in the first 3 years of follow-up were considered in the model. Patients classified at baseline with BODE class 2 (HR: 2.62, 95% CI: 1.36-5.04; P=0.004), BODE class 3 (HR: 2.54, 95% CI: 1.15-5.61; P=0.02), and BODE class 4 (HR: 15.35, 95% CI: 3.11-75.75; P=0.001) showed increased risk of death compared to those with BODE class 1. The CCI (HR: 1.29, 95% CI: 1.00-1.68; P=0.04) and the number of exacerbations in the first 3 years (HR: 1.32, 95% CI: 1.00-1.76; P=0.04) also showed increased risk of death. By replacing the BODE index for the variables that compose it, those with body mass index ≤21 kg/m 2 showed increased risk of death compared to those with body mass index (BMI)>21 kg/m 2 (HR: 2.70, 95% CI: 1.38-5.25; P=0.003). Conclusion: After 9 years, we identified that those with high BODE index, greater CCI, greater frequency of exacerbations in the first 3 years, and BMI #21 kg/m2 showed increased risk of death.
Keywords: COPD; Disease severity index; Mortality